Cover Image. Issue 10 (3rd October 2022) - Lalonde, Robert L.; Kemmler, Cassie L.; Riemslagh, Fréderike W.; Aman, Andrew J.; Kresoja‐Rakic, Jelena; Moran, Hannah R.; Nieuwenhuize, Susan; Parichy, David M.; Burger, Alexa; Mosimann, Christian
Abstract : Ventral view of a 3 day‐old zebrafish in which lateral plate mesoderm‐derivatives including the heart were lineage‐labeled (magenta) using transgenes for drl:creERT2 and the loxP‐based reporter ubi:Switch (brightfield and mCherry fluorescence composite, 20x lens, Zeiss LSM 880 confocal). From: Heterogeneity and genomic loci of ubiquitous transgenic Cre reporter lines in zebrafish ; Lalonde RL Kemmler CL, Riemslagh FW, Aman AJ, Kresoja‐Rakic J, Moran HR, Nieuwenhuize S, Parichy DM, Burger A, Mosimann C. Developmental Dynamics . 251(10): 1754–1773. https://doi.org/10.1002/dvdy.499